Music Acculturation in Rhythm of kapang-kapang Bedhaya and Srimpi Dance in the Keraton of Yogyakarta (A Case Study) - R.M. Surtihadi (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
The research’s aim is to notice the music acculturation in the rhythm of female dance of Bedhaya and Srimpi dances in the Kingdom of Yogyakarta on the line-movement on-to the stage or leaving it (kapang-kapang). Besides, the research is going to discuss a West music instrument acculturation phenomenon with Javanese Traditional Gamelan Orchestra on the rhythm of female dance of Bedhaya and Srimpi dances that are still exist nowadays. The case study is focus on the usage of some West music instrument such as drum (percussion section), woodwind (woodwind section), brass-wind (brass-wind section), and stringed (stringed section) in the rhythm of the dances which are being mentioned above. The method which is being used first is by doing the quality data analysis. The result of the research are two mainly findings; those are 1) the inclusion of various elements of the palace ceremonial ritual by The Netherlands Indies government which were the impact of the European Colonization in the island of Java, especially in Yogyakarta; it has made a mentally structure of the people of Yogyakarta that would have created culture capitalized and which are being used in the context of Yogyakarta as the city of culture. 2) European military music for marching is being the inspiration of the palace to create Gendhing Mars which is being used as the rhythm in the marching movements of female dancers (kapang-kapang) together along with the ensemble of Javanese Traditional Gamelan Orchestra and the European music instruments which are being played in one sound (unisono).